2014
DOI: 10.1166/jbt.2014.1230
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Finite Element Study to Characterize the Influence of Load Direction on Stress Distribution in Bone Around Dental Implant

Abstract: This study aimed to establish a three-dimensional (3D) finite element model for variation of loading direction to identify its effects on the stress distribution generated around an implant and surrounding jawbone under biomechanical consideration. Twenty one 3D finite element cases containing the endosseous titanium implant in type II bone under three different loads i.e., 50, 100, and 200 N, with various directions from 0 to 30 degrees to the vertical axis with the increasing rate of 5 degrees were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…On the contrary, oblique load creates shear forces and lateral movements on the implant, thus leading to more stress on the surrounding bone. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, oblique load creates shear forces and lateral movements on the implant, thus leading to more stress on the surrounding bone. [ 29 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to Guan et al, different stress characteristics are produced by different sizes of implant surface contact areas (Guan, van Staden, Johnson, & Loo, 2011). Shamami et al state that the loading direction has a significant effect on the maximum stress values and stress distribution patterns in the implant/bone system (Shamami, Karimi, Beigzadeh, Derakhshan, & Navidbakhsh, 2014). Their continuous dynamic study emphasized that the size and shape of the thread geometry contacting the bone was a major factor characterizing the stress profile in the surrounding bone.…”
Section: Effect Of the Dental Implant Design On Stress Distributionmentioning
confidence: 99%
“…The implantation process distributes complex loading forces in various directions to the surrounding bone (Shamami, Karimi, Beigzadeh, Derakhshan, & Navidbakhsh, 2014). The loading direction has a significant effect on the maximum stress values and stress distribution patterns in the implant/bone system.…”
Section: The Importance Of the Relationship Between The Final Drillmentioning
confidence: 99%
“…Dental implants have become increasingly common as a method for replacing missing teeth in recent decades [1][2][3][4]. However, while some studies have reported an implant success rate as high as 78-100% [5], other studies have indicated that single tooth replacement failures may occur for a variety of reasons [6], including implant surface, implant design, and bone quality factors [7] and early bone loss in the dental implant region [8]. Numerous studies have found a link between the success of dental implants, the biological tissue structure of the bone, the mechanical strength of the bone and implant, and the surgical technique employed to insert the implant [6,9,10].…”
Section: Introductionmentioning
confidence: 99%